Treatment intensification followed by interleukin-7 reactivates HIV without reducing total HIV DNA: a randomized trial. (January 2016) - Katlama, Christine; Lambert-Niclot, Sidonie; Assoumou, Lambert; Papagno, Laura; Lecardonnel, François; Zoorob, Rima; Tambussi, Giuseppe; Clotet, Bonaventura; Youle, Mike; Achenbach, Chad J.; Murphy, Robert L.; Calvez, Vincent; et al.
Abstract : Background: As a first step towards HIV cure, we assessed a strategy of antiretroviral therapy (ART) intensification followed by interleukin-7 (IL-7) used as an HIV-reactivating agent. Methods: A multicentre, randomized clinical trial included patients on suppressive ART with CD4 + cell counts at least 350/μl and HIV-DNA between 10 and 1000 copies/10 6 peripheral blood mononuclear cells (PBMCs). After an 8-week raltegravir and maraviroc intensification, patients were randomized to intensification alone or with 3 weekly IL-7 injections at weeks 8, 9 and 10. The primary endpoint was at least 0.5 log10 decrease in HIV-DNA in PBMC at W56. Secondary endpoints included ultrasensitive plasma viremia, immunologic changes and safety. Results: Twenty-nine patients were enrolled with median baseline 558 CD4 + cell counts/μl, 360 HIV-DNA copies/10 6 PBMCs and 12 years on ART. No patient in either arm achieved the primary endpoint. Addition of IL-7 induced a significant expansion of CD4 + T cells, primarily central-memory cells (+5%, P  = 0.001) at week 12, together with an increase in levels of HIV-DNA/10 6 PBMC (+0.28 log10  copies/ P  = 0.001), and the proportion of patients with detectable ultrasensitive plasma HIV-RNA increased compared with week 8 ( P  = 0.07). At weeks 56 and 80, total and memory CD4 + cell counts and total HIV-DNA/ml of blood remained elevated. In contrast, HIV-DNA/million PBMC and plasma viremia returned to baseline levels whereas activated HLA-DR + CD4 + T cells significantly decreased. Conclusion: IL-7 administration and dual ART intensification induced, despite a mild HIV reactivation, an amplification of the HIV reservoir, as a result of central-memory CD4 + T-cell expansion, thus limiting this IL-7 based strategy. Clinical trial registration: This trial was registered with ClinicalTrials.gov, number NCT01019551. Abstract : Supplemental Digital Content is available in the text